Eksplorasi Desain Kurikulum dan Penerapan Tipe Pembelajaran Kooperatif di SMP Muhammadiyah 14 Surabaya - Indriana, Mei Riska; Nurjannah, Rosa Nilla; Maulanasyah, Dimas Rizki; Wulandari, Ayu (Lembaga Yasin AlSys, 2024)
Teachers in junior high schools need to gain the knowledge, skills and support necessary to integrate cooperative learning methods into learning programs. There needs to be an update in curriculum design to accommodate these learning strategies and ensure the achievement of educational goals with efficiency. Exploring curriculum design to implement cooperative learning methods for teachers in junior high schools is a very relevant and important step in responding to the demands of current developments. This research method involves interviews with the Head of Curriculum as a resource person and uses the Project Based Learning (PJBL) learning model at SMP Muhammadiyah 14 Surabaya. The results of implementing this learning model include two aspects, namely the work or projects produced by students and the development of a sense of concern for the problems they face. Apart from that, there is a relationship between learning the Merdeka curriculum and the P5 program (Project for Strengthening the Profile of Pancasila Students). In conclusion, exploring curriculum design and implementing cooperative learning in junior high schools requires an in-depth understanding of student needs and characteristics, as well as the educational goals to be achieved. A good curriculum will include material that is developmentally appropriate for students and provides opportunities for them to be actively involved in the learning process. However, the implementation of cooperative learning in junior high schools is also faced with a number of challenges.